No, Brettanomyces bruxellensis is not responsible for all woes! - Pierre Moulis; Cécile Miot-Sertier; Céline Franc; Laurent Riquier; Stéphanie Marchand; Gilles de Revel; Doris Rauhut; Patricia Ballestra (IVES Technical Reviews, 2023)
In wines, rice cake and sausage skin aromas are generally associated with the alteration of mousy off-flavours and constitute an increasingly prevalent deviation in some wines. In the present study microorganisms present in 25 altered wines were isolated. The spoilage yeast Brettanomyces bruxellensis, and lactic acid bacteria of the species Oenococcus oeni and Lentilactobacillus hilgardii were identified, and their ability to produce the N-heterocycles responsible for the mousy off-aroma was deterimined. B. bruxellensis was found in a minority of the wines altered by the mousiness.